The Implications of Halal Regulations in Indonesia: A Consumer Protection’s Legal Perspective - Yuanitasari, Deviana; Sardjono, Agus; Susetyo, Heru (Faculty of Law, Universitas Padjadjaran, 2024)
Indonesia is a Muslim-majority country that requires the state’s ability to protect Muslim populations’ religious practices. Muslims are obliged to eat halal food and beverages. Muslims may now easily purchase halal goods because of Law Number 8 of 1999 and Law Number 33 of 2014, which guarantees the authenticity of halal products. Muslims make up a sizable and potentially influential market segment, making this legislation even more crucial. The Law Number 6 of 2023 on Job Creation has revised many laws, including the Law Number 33 of 2014. Nevertheless, this rule was short-lived. Micro and small enterprises may get free halal certification with a business statement under the previous regulations. This free certification aims to let Muslim customers get halal items faster and more efficiently. This study aims to determine the impact on the field with the enactment of Law Number 6 of 2023 on implementing halal certification for micro and small businesses to protect Muslim consumers. This study used secondary data and employed normative legal methodologies. It reveals that halal certificates are defined differently in different regulations. The inconsistent definitions affect micro and small businesses' halal certification and halal certificates’ validity period. Customers' trust in small stores and other small enterprises may rise or fall indefinitely, depending on the prospect of validity.